THE LEVERAGE, ARUS KAS BEBAS, KARAKTERISTIK PERUSAHAAN, DAN MANAJEMEN LABA - Allbestin Primalestari; Tjhai Fung Jin (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2022)
This study aims to obtain empirical evidence and analyze the influence of leverage, motivational bonuses, free cash flow, firm size, board size, size of audit committee, independent commissioners, managerial ownership, and institutional ownership as independent variables on earnings management as a dependent variable. The company used in this research is non-financial companies that listed on Indonesian Stock Exchange (IDX) consistently from 2017 to 2020. There are 66 companies which have 264 data meet the criteria by using purposive sampling method. This study uses multiple regression models for data analyst and uses Modified Jones Model to estimate the value of discretionary accruals as the proxy of earnings management. The result of this study show that leverage, free cash flow, and board size have an influence on earnings management. However, other variables such as motivational bonuses, firm size, size of audit committee, independent commissioners, managerial ownership, and institutional ownership do not have an influence on earnings management.